(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The ability to perform the crescent kick is one of the basic techniques that determines the success of athletes in pencak silat, so an appropriate physical training program is needed to improve the quality of the movement. This study aims to analyze the effect of explosive leg and back muscle training on the ability to perform the crescent kick in extracurricular activities at SD Negeri 1 Baler Bale Agung. This study used an experimental method with a Two Groups Pretest–Posttest Design. A sample of 30 participants was selected through simple random sampling and divided into an experimental group and a control group. The experimental group was given an explosive leg and back muscle training program for 12 meetings, while the control group was not given any special treatment. Data were obtained through a 30-second crescent kick ability test and analyzed using descriptive statistical tests, normality tests, homogeneity tests, paired sample t-tests, and independent samples t-tests. The results showed that the experimental group experienced a higher increase in crescent kick ability compared to the control group. This difference was proven to be statistically significant (p < 0.05), which indicates that explosive leg and back muscle training is effective in improving crescent kick ability. Thus, explosive strength training needs to be integrated into the pencak silat training program to improve the performance of students’ basic techniques.